Researches in Corporate Social Responsibility: A Review of Shifting Focus, Paradigms, and Methodologies - Taneja, Shallini S.; Taneja, Pawan Kumar; Gupta, Rajen K. (2011)
Owing to the growing academic and practitioner’s interest in the field of Corporate Social Responsibility, there is a need to do a comprehensive assessment and synthesis of research activities. This article addresses this need and examines the academic literature on Corporate Social Responsibility and Performance using a paradigmatic and methodological lens. The objective of this article is fourfold. First, it examines the status of CSR research from its beginning especially after 1970 to year 2008 in leading academic journals and reports to assess the focus areas of research on CSR so far. Second, it analyzes the research paradigms adopted in these research articles using the Operations Research Paradigm framework. Third, it compares and contrasts various kinds of research articles, methodologies, and research designs used in various researches in literature. Finally, it uncovers the implications of this study and directions for future research.
Keywords: N01; M14; paradigm shifts; research paradigms; Literature Review; methodological review; Corporate Social Performance; Corporate social responsibility (CSR)